Refractory chyle leakage after laparoscopic cholecystectomy for gallstone disease: A case report and literature review. Issue 2 (January 2018) - Yao, Bao Z.; Li, Liang; Jiang, Ming; Wang, Jie; Zhang, Jun
Abstract: Rationale: Gallstone disease is commonly worldwide and safely treated by laparoscopic cholecystectomy. Chylous ascites is a rare but serious complication of many abdominal operations. Patient concerns: We present a rare case of refractory chyle leakage post-LC for acute cholecystitis that is successfully treated in a 40-year-old man, and review current literature on the prevalence, diagnosis, and management of this complication. Diagnoses: Refractory chyle leakage post-LC, a rare but serious complication after laparoscopic cholecystectomy. Interventions: Conservative treatment was given initially; however, the outcome was frustrating. Surgical intervention was given without further delay. Outcomes: After the reoperation, conservative treatment was still maintained. After nearly 8 months of treatment, the patient recovered and then was discharged. Lessons: This case represents a previously unreported complication of refractory and high flow chyle leakage after laparoscopic cholecystectomy, which did not improve alter conservative management with dietary changes and other measures. So we suggest that surgical intervention should be given for refractory cases without further delay. It can not only shorten the disease progression, but also alleviate the sufferings of the patient.